Socioeconomic Disparities in the Prevalence of Cardiometabolic Risk Factors in Ghanaian Women - Jeffrey Boakye; Danielle Mensah; Swati Sakhuja; Pauline E. Jolly; Tomi Akinyemiju (Ubiquity Press, 2017)
Background: Recent trends toward urbanization in developing countries like Ghana, coupled with nutritional transition and aging populations, have led to a rapid increase in the prevalence of noncommunicable diseases such as obesity, diabetes, and hypertension. The purpose of this study was to evaluate the association between socioeconomic status and cardiometabolic risk factors among women in Ghana. Methods: Data for this analysis were obtained from Wave 1 of the Ghana Study of Global Aging and Health, conducted in 2007, and included women 18 years and older. Survey weighted descriptive and multivariable linear regression models were used to examine the association between socioeconomic status and cardiometabolic risk factors. Results: Among a total of 1988 women, 48% ages 40-64 years, almost half were overweight or obese (47%) and 21% had current hypertension, whereas only 4.3% and 2% of women self-reported a history of hypertension and diabetes, respectively. Multivariable adjusted analysis indicated that women with a high school education had 2-fold increased odds of being overweight or obese compared with those with no formal education (odds ratio [OR]: 2.02, 95% confidence interval [CI]: 1.20-3.42). Women employed in the public sector had almost a 5 times higher odds of being overweight or obese (OR: 4.94, 95% CI: 1.42-17.15), whereas those employed in the private sector or self-employed had reduced odds of diabetes (OR: 0.27, 95% CI: 0.10-0.70) and hypertension (OR: 0.43, 95% CI: 0.21-0.86). Conclusion The prevalence of cardiometabolic risk factors varies by socioeconomic status among Ghanaian women. Targeted intervention programs to reduce overweight and obesity may begin among Ghanaian women employed in the public sector, and improved access to health care will be critical for timely diagnosis and management of other disease risk factors.